The Amorites : A Political History of Mesopotamia in the Early Second Millennium BCE - Wasserman, Nathan, (Culture and History of the Ancient Near East ;, 2023)
This study of the political history of Mesopotamia - today's Iraq and Syria - in the Old Babylonian period (ca. 2000-1600 BCE) is the first comprehensive historical synthesis of this kind published in English after many decades. Based on numerous written sources in Sumerian and Akkadian - royal inscriptions, letters, law collections, economic records, etc. - and on up-to-date research, it presents the region's political history in a meticulous geographic and chronological manner. This allows the interested academic and non-academic reader an in-depth view into the scene of ancient Mesopotamia ruled by competing dynasties of West Semitic (Amorite) origin, with a complex web of political and tribal connections between them.